RIBA IN TIME VALUE OF MONEY CONCEPT PERSPECTIVE OF SHARIA LAW - Arifin S; Dini Maulana Lestari; Reni Furwati (Institut Agama Islam Negeri (IAIN) Bone, 2021)
AbstractRiba is a soul of conventional economy system. Every transaction activityin that system has strong correlation withit. Furthermore, riba becomes the main basic foundation of investment tool regarding to evaluating such a proper investment in conventional financing system. The certain view of time value of money concept is positive time preference toward an investment, it means that such an investment definitely would give a profit which is full of riba due to discount rate method calculation as the main analysis tools, and of course that comprehension is contradict through Islamic economy concept. Nevertheless, is that analysis investment method forbidden if it applies on such an investment which is no riba into it, or are the investors wrong if they would like to get such a surplus or benefit from the investment? This research discusses the concept of riba in time value of money theory. Also, this is kind of qualitative research with library method approach. As the result, this research delineates that time value of money is containing riba in the term of concept. However, if this concept is only used as the analysis tool regarding to knowing and evaluating such investment (read-without riba) proper or improper, it could not be catagorized as riba. Keywords: Riba, Time value of Money, Investment, Sharia Law.